2011
DOI: 10.1007/s12013-011-9208-2
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Enhanced Power Doppler Imaging in Monitoring Acral Microcirculation in Type 2 Diabetes Mellitus and its Complications

Abstract: This study compared hemodynamic changes of acral arterioles (pulps and nail beds of fingers and toes) and the microcirculatory status of acra between patients with uncomplicated (n = 45) or complicated (n = 36) type 2 diabetic mellitus (type 2 DM) and healthy subjects (n = 40). Enhanced power Doppler imaging (e-Flow) was used to display the nail bed arterioles and distal branches of pulp arterioles (digitales palmares propriea and digitales plantares propriea) in the end knuckle of the right middle finger and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Similar hemodynamic alterations in the arterioles of the finger and toe in patients with DM were observed by Ma et al [ 27 ] using an e-flow Doppler technique, which was developed from the power Doppler sonographic method. Although blood flow in the acral finger arterioles could be shown by the e-flow Doppler technique, the flow hemodynamic parameters (PSV and EDV) measured by the e-flow Doppler technique were collected in a conventional manner with only one sampling line or sampling point.…”
Section: Discussionsupporting
confidence: 74%
“…Similar hemodynamic alterations in the arterioles of the finger and toe in patients with DM were observed by Ma et al [ 27 ] using an e-flow Doppler technique, which was developed from the power Doppler sonographic method. Although blood flow in the acral finger arterioles could be shown by the e-flow Doppler technique, the flow hemodynamic parameters (PSV and EDV) measured by the e-flow Doppler technique were collected in a conventional manner with only one sampling line or sampling point.…”
Section: Discussionsupporting
confidence: 74%
“…The mean age and ankle-brachial indexes are 56. 13 The blood vessel diameter and arterial thickness were significantly larger in the diabetes group as compared to the control group (Table 2, Figure 5). There were no significant differences in color Doppler lumen diameters between cases and controls ( The PI of both DPA and RI of right DPA increased in diabetic patients compared to the controls without significant difference (p>0.05) and so the RI in the left PTA (Table 2).…”
Section: Resultsmentioning
confidence: 90%
“…This might be attributed to chronic hyperglycemia, a predisposing risk factor to diabetes-related angiopathies [12]. The increase in flow resistance might also suggest changes in blood vessel walls (wall stiffening), which affects Doppler flow parameters [13].…”
Section: Discussionmentioning
confidence: 99%
“…Doppler flow parameters were also not sensitive indicators of changes in the natural history of diabetes in early periods. 26 Ma et al 27 adopted enhanced power Doppler imaging (e-Flow) to display the acral arterioles (pulps and nail beds of fingers and toes) and the microcirculatory status. They found that although e-Flow was superior to the conventional ultrasound in improving the sensitivity of blood flow signals, there was uncertainty in the display of microcirculation.…”
Section: Discussionmentioning
confidence: 99%